2019
DOI: 10.1055/s-0039-1688949
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcomes of All-Arthroscopic Pre-Tied Suture Device Triangular Fibrocartilage Complex Repair

Abstract: Background A pre-tied suture device has been utilized for all-arthroscopic peripheral triangular fibrocartilage complex (TFCC) repairs with promising early clinical results. Purpose The purpose of this study was to evaluate long-term functional outcomes of these repairs. Patients and Methods A retrospective review of patients undergoing arthroscopic TFCC repair was performed. Inclusion criteria were the Palmer type 1B TFCC tears diagnosed on arthroscopy and repaired using the all-arthro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…The all-arthroscopic technique using a pre-tied suture device in peripheral TFCC tear was rst published by Yao et al in 2007 [20]. Long-term report at a mean 7-year follow-up in Palmer IB lesion without gross DRUJ instability exhibits promising outcome [21]. We adapt this pre-tied suture device for use in the treatment of peripheral TFCC tear with proximal component involvement.…”
Section: Discussionmentioning
confidence: 99%
“…The all-arthroscopic technique using a pre-tied suture device in peripheral TFCC tear was rst published by Yao et al in 2007 [20]. Long-term report at a mean 7-year follow-up in Palmer IB lesion without gross DRUJ instability exhibits promising outcome [21]. We adapt this pre-tied suture device for use in the treatment of peripheral TFCC tear with proximal component involvement.…”
Section: Discussionmentioning
confidence: 99%
“…Three papers were comparative studies and included two study groups. 26,40,48 Fourteen studies reported peripheral TFCC repairs [26][27][28][29][30][31][32][33][34][35][36][37][38][39] and 13 studies reported foveal avulsions of the TFCC. [40][41][42][43][44][45][46][47][48][49][50][51][52] As the pathoanat-omy of these tears and repair techniques differ, the outcomes of peripheral and foveal tears were analyzed separately.…”
Section: Study and Patient Characteristicsmentioning
confidence: 99%
“…Miwa et al proceeded to surgery after 2 months with persistent "unendurable pain." 9 Tang et al, 10 Kim et al, 11 Sarkissian et al, 12 and Iwasaki et al 13 all moved to surgery after 3 months with Iwasaki et al using a removal wrist brace for immobilization. Ruch and Papadonikolakis 14 and Infanger and Grimm 15 proceeded after at least 4 months of conservative management and Papapetropoulos et al, 16 Bayoumy et al, 17 and Millants et al 18 utilized 6 months of conservative management with splinting and anti-inflammatories prior to surgical intervention.…”
Section: Nonoperative Treatmentmentioning
confidence: 99%
“…In our review, 16 articles were found focusing specifically on outcomes of arthroscopically repaired 1B lesions with a total of 409 patients undergoing repair. [11][12][13][16][17][18][38][39][40][41][42][43][44][45][46][47] For the 16 articles, four different scoring metrics were reported (Disabilities of the Arm, Shoulder, and Hand [DASH], Mayo, visual analog scale, and personal scoring system) and not every article reported pre-and postoperative values. Additionally, not all reported range of motion (ROM), pain, or return to work status.…”
Section: Repairmentioning
confidence: 99%
See 1 more Smart Citation